ANALISIS ANGGARAN BIAYA OPERASIONAL USAHA JASA PERHOTELAN TERHADAP PENINGKATAN LABA PADA AL BADAR HOTEL SYARIAH MAKASSAR - ali, muhammad ridwan; Putra, Trisno Wardy (Jurnal Ar-Ribh, 2019)
This study aims to find out to determine the increase in profits through budget analysis based on the realization of the operational budget at Al Badar Hotel Syariah Makassar. The data analysis technique used in this study is quantitative descriptive analysis. Sources of data used in this study are primary data in the form of conducting interviews and secondary data, namely data that has been further processed, namely reports on the operating costs of hospitality services business to increase profits at Al Badar Makassar Islamic Hotels. The results of this study are where in the preparation of the budget carried out by the hotel is not flexible from year to year or other words are too static (fixed) so that it cannot stem changes in costs incurred. Budgeting for operational costs is so important in the activities of a business that is engaged in trading, industrial business and service business, in an effort to increase profits regarding controlling operational costs cannot be ruled out because this is so important in supporting the performance of operational activities.